Social Actors and Flood in Jakarta - Meyza Pritama (Universitas Pendidikan Indonesia (UPI), 2014)
This present study examined the representation of Social Actors in articles from an online newspaper centroone.com about the flood in Jakarta in 2013 by using van Leeuwen’s social actor network (2008). This study employed qualitative method to describe the representation and its significance. The collected data were 9 articles from an online newspaper centroone.com. The data were analyzed in the unit of words and sentences to reveal the representation of the social actors. The study disclosed that in the articles, the social actors were represented through the use of 6 ways, namely proper names, pronouns, social titles, institutions, general groups, and nouns. The representations then indicated 3 significant actors related to the flood in Jakarta in 2013: Joko Widodo, BNPB, and the citizens. Joko Widodo was indicated as the work of the government of Jakarta, BNPB was indicated as the work performed by the institution, not the institution, and the citizens was indicated as the people related to the flood; as the citizens and the victims.Keywords: Social Actors, Critical Discourse Analysis, Representation